2017
DOI: 10.18001/trs.3.2(suppl1).6
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Cigarillo Initiation and Cigarillo Manipulation Methods among Adolescents

Abstract: Objective To understand reasons for cigarillo initiation and cigarillo manipulation methods among adolescents. Methods We conducted surveys in 8 Connecticut high schools to assess reasons for trying a cigarillo and cigarillo manipulation methods. We used multivariable logistic regressions to assess associations with demographics and tobacco use status. Results Among ever cigarillo users (N = 697, 33.6% girls, 16.7 years old [SD = 1.14], 62.1% White), top reasons for trying a cigarillo were curiosity (41.9%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 46 publications
(59 reference statements)
1
21
0
Order By: Relevance
“…Flavored cigars are popular among youth, 37,38 and appealing flavors are cited as the most common reason for cigar initiation among adolescents. 13 We observed that flavors were critically important in creating a blunt. Participants enjoyed trying a new cigar flavor; specifically, they reported liking the aroma when first opening the package, as well as the taste from licking the wrapper, and taking the initial puffs.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Flavored cigars are popular among youth, 37,38 and appealing flavors are cited as the most common reason for cigar initiation among adolescents. 13 We observed that flavors were critically important in creating a blunt. Participants enjoyed trying a new cigar flavor; specifically, they reported liking the aroma when first opening the package, as well as the taste from licking the wrapper, and taking the initial puffs.…”
Section: Discussionmentioning
confidence: 93%
“…11 These inexpensive cigars like cigarillos or little cigars are widely available and have features that are appealing to youth, such as enticing flavors and packaging. 12,13 Cigars also are widely used by youth to co-use tobacco and marijuana by creating blunts; about two-thirds of adolescent cigar users 14 and nearly half of young adult cigar users report that they are using cigars to create blunts. 15…”
mentioning
confidence: 99%
“…The sensory attractiveness of LCCs, both flavored and regular, has been well documented as a key reason for smoking them. 25 , 28 , 29 , 32 Regulation that would ban flavorings could potentially decrease the prevalence of cigar initiation. The importance of the social context of smoking has also been noted.…”
Section: Discussionmentioning
confidence: 99%
“…LCCs are sold singly and/or in small packs of two or three, and are not taxed at the same rate as cigarettes, making them an affordable alternative for many. 25 , 32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation